2021
DOI: 10.1186/s12931-021-01845-2
|View full text |Cite
|
Sign up to set email alerts
|

Does bronchial hyperresponsiveness predict a diagnosis of cough variant asthma in adults with chronic cough: a cohort study

Abstract: Bronchial hyperresponsiveness is a typical, but non-specific feature of cough variant asthma (CVA). This study aimed to determine whether bronchial hyperresponsiveness may be considered as a predictor of CVA in non-smoking adults with chronic cough (CC). The study included 55 patients with CC and bronchial hyperresponsiveness confirmed in the methacholine provocation test, in whom an anti-asthmatic, gradually intensified treatment was introduced. The diagnosis of CVA was established if the improvement in cough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…In contrast, measurement of FeNO and bronchial hyperresponsiveness is of great value to exclude or diagnose cough variant asthma especially in sensitized patients [8,10,17,26]. A recent study confirmed the high positive predictive value of bronchial hyperresponsiveness in patients with cough variant asthma [25].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, measurement of FeNO and bronchial hyperresponsiveness is of great value to exclude or diagnose cough variant asthma especially in sensitized patients [8,10,17,26]. A recent study confirmed the high positive predictive value of bronchial hyperresponsiveness in patients with cough variant asthma [25].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we did not observe correlation between PC 20 and response to anti-asthmatic therapy in patients with CVA either. 19 …”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we did not observe correlation between PC 20 and response to anti-asthmatic therapy in patients with CVA either. 19 Moreover, there is paucity of data on noneosinophilic phenotype of CVA so far. Gao et al compared classic asthma and CVA, showing more severe BHR, a lower percentage of eosinophils and higher neutrophils in induced sputum cell count in CVA, which probably indicated different airway inflammatory subtypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 A positive bronchial provocation test is the gold standard for the diagnosis of CVA. 18 The methacholine bronchial provocation test is essential in the diagnosis of chronic cough related to bronchial hyperresponsiveness, 19 and FeNO is one of the non-invasive indicators for observing airway inflammation. FeNO cannot replace the bronchial provocation test, 20 however, its detection can be employed in conjunction with other indicators to comprehensively…”
mentioning
confidence: 99%